Outcomes and considerations for retrograde intrarenal surgery (RIRS) in the setting of multiple and large renal stones (>15 mm) in children: Findings from multicentre and real-world setting - ŞEKERCİ, ÇAĞRI AKIN (My University, 2024)
Purpose: The aim of this study is to evaluate the outcomes of retrograde intra renal surgery (RIRS) in the setting of large or multiple stones in children (15 mm, or both. Outcomes included stone free rate (SFR) and complications within 30 days. Results: In total, 344 patients were included with 197 and 147 in Groups 1 and 2, respectively. Ureteric access sheaths were more frequently used in Group 2 (39.5% vs. 56.8%, p = 0.021). The operation time was significantly longer in Group 2 (p < 0.001). SFR after a single procedure was 84.7% in Group 1 and 63.7% in Group 2. Overall complication rates in Groups 1 and 2 were 7.6% and 33.3%, respectively. The most frequently reported complication in both groups was post-operative fever (4.4% vs. 14%, p = 0.004). The rate of Clavien I/II complications in groups 1 and 2 was 6% and 25.1%, respectively (p < 0.05). The rate of Clavien ≥ III complications in groups 1 and 2 was 1.6% and 8.1%, respectively (p < 0.05). On multivariate analysis, total operation time, stone size and multiplicity were significant predictors of residual fragments. Conclusions: RIRS can be performed in paediatric cases with large and multiple stone burdens, but the complication rate is significantly higher when compared to smaller stones.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Onkoloji; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Oncology; Surgery Medicine Sciences; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; CERRAHİ; ONKOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; SURGERY; ONCOLOGY; Üroloji; Cerrahi; Urology; Surgery; paediatric; renal stone; retrograde intrarenal surgery; ureteroscopy; urolithiasis